2000
DOI: 10.1177/104973150001000506
|View full text |Cite
|
Sign up to set email alerts
|

The Client Satisfaction Inventory: Results of an Initial Validation Study

Abstract: Objective: To obtain initial results with regard to the reliability and validity of the Client Satisfaction Inventory (CSI), a 25-item scale for measuring general satisfaction with services among clients of human service agencies. Method: The CSI was administered to 329 clients of 11 agencies in six states. Also administered were three other standardized measures and a brief descriptive questionnaire, results from which were used to assess the discriminant validity of the CSI. Results: Findings indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
6
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 34 publications
2
53
6
4
Order By: Relevance
“…Leibert et al (2006) showed that the clients, primarily young white women, rated themselves as satisfi ed with online mental health counseling and had established a working alliance with their mental health counselors. However, the levels of both satisfaction and working alliance were not as strong as levels reported in past studies involving face-toface mental health counseling (Busseri & Tyler, 2003;McMurtry & Hudson, 2000). Nevertheless, clients reported experiencing greater ease in selfdisclosing with their Internet mental health counselors compared to self-disclosing with face-to-face counselors, especially during the beginning stages of counseling.…”
Section: Disinhibition Theorycontrasting
confidence: 54%
“…Leibert et al (2006) showed that the clients, primarily young white women, rated themselves as satisfi ed with online mental health counseling and had established a working alliance with their mental health counselors. However, the levels of both satisfaction and working alliance were not as strong as levels reported in past studies involving face-toface mental health counseling (Busseri & Tyler, 2003;McMurtry & Hudson, 2000). Nevertheless, clients reported experiencing greater ease in selfdisclosing with their Internet mental health counselors compared to self-disclosing with face-to-face counselors, especially during the beginning stages of counseling.…”
Section: Disinhibition Theorycontrasting
confidence: 54%
“…This study was also limited because it involved a relatively homogeneous sample of college students. Liebert et al (2006) studied a group of eighty-one primarily female clients using online services examining self-reported therapeutic alliance and satisfaction variables, compared to past face-to-face studies by McMurtry and Hudson (2000) and Busseri and Tyler (2003). Liebert et al found that the more hours respondents spent online, the more likely they were to make use of online counselling.…”
mentioning
confidence: 99%
“…Initial validation results indicate good reliability for both the CSI and CSI-SF at .93 and .89, respectively, with a correlation of .94 between their scores (McMurtry & Hudson, 2000). Findings also provided support for the construct validity of the two versions, as indicated by the absence of correlations between scores on each measure and demographic characteristics of the test participants.…”
mentioning
confidence: 59%
“…The CSI is a 25-item scale designed to measure service satisfaction as a single dimension among clients receiving diverse types of human services (McMurtry & Hudson, 2000). Its brief version, the CSI-Short Form (CSI-SF), consists of a subset of 9 items from the full version.…”
mentioning
confidence: 99%